Abortion, Time-Relative Interests, and Futures Like Ours - Nichols, Peter (Ethical theory and moral practice, 2012)
Don Marquis (1989) has argued most abortions are immoral, for the same reason that killing you or me is immoral: abortion deprives the fetus of a valuable future (FLO). Call this account the FLOA. A rival account is Jeff McMahan’s (2002), time-relative interest account (TRIA) of the wrongness of killing. According to this account, an act of killing is wrong to the extent that it deprives the victim of future value and the relation of psychological unity would have held between the victim at the time of death and herself at a later time if she had lived. The TRIA supposedly has two chief advantages over Marquis’s FLOA. First, unlike the FLOA, the TRIA does not rely on the controversial thesis that identity is what matters in survival. Second, the TRIA yields more plausible verdicts about cases. Proponents of the TRIA use the account to argue that abortion is generally permissible, because there would be little to no psychological unity between the fetus and later selves if it lived. I argue that advocates of the TRIA have failed to establish its superiority to the FLOA, for two reasons. First, the two views are on a par with respect to the thesis that identity is what matters in survival. Second, Marquis’s FLOA does not yield the counterintuitive implications about cases that advocates of the TRIA have attributed to it, and the TRIA yields its own share of implausible judgments about cases.